Riqueza ictiofaunística e aspectos hidrogeomorfológicos de rios e riachos das regiões de cabeceira e de planície de inundação da Bacia Tocantins-Araguaia, Brasil Central - Araújo, Nicelly Braudes (2012)
This study aims to characterize the hydromorphological variables that structure the ichthyofauna and see if there is difference in the estimated species richness and species richness of families and trophic groups between the rivers and streams sampled and between the headwaters of the Araguaia and Tocantins basins and different environments sampled, floodplain and regions of the head. The samples were taken from 30 watercourses, of which 12 belong to the basin of the Tocantins and Araguaia basin to 18. For analysis of the ichthyofauna were considered species richness and abundance of individuals of families and trophic groups. The variables considered were pH, conductivity, dissolved oxygen, water velocity, width, depth, light and turbidity. The results showed that the location of watercourses in the floodplain of the Araguaia River basin or in the regions of the head independent of the basin was the main factor that defines both the number of species and the similarity of the ichthyofauna. The streams included in the flood plain of the Araguaia basin that are favored by the heterogeneity of the habitat had the highest number of species. Instead, the head of watercourses, shallow, narrow and with the presence of rocks, which are characterized by reduced habitat had low values of richness of the fauna, which was structured by varying pH and conductivity. On the other hand, as the species richness of families and trophic groups no significant difference between the headwaters of the Araguaia and Tocantins river basins, however between different environments, headboard and plain, the basin of the Araguaia River, this difference was significant. Among the regions of the headwaters of the Araguaia and Tocantins river basins, both families and trophic groups are more species-rich at the points of the head of the Tocantins, because, despite their similar characteristics, the majority of the data points presented in the headwaters of the Tocantins be more conservative with respect to the presence of riparian vegetation. On the other hand, the species richness of families and trophic groups in the different environments sampled in the Araguaia basin, plain and headboard, showed that the lowland region is richer in species, which presents important feature, the heterogeneity of habitat that offers great diversity of shelter and food resources.